Osteopontin enhances multi-walled carbon nanotube-triggered lung fibrosis by promoting TGF-β1 activation and myofibroblast differentiation - Jie Dong; Qiang Ma (Particle and Fibre Toxicology, 2017)
Abstract Background Carbon nanotubes (CNTs) have been used in a variety of applications because of their unique properties and functions. However, many CNTs have been shown to induce lung fibrosis in experimental animals with some at a potency greater than that of silica, raising concern over possible toxic effects of CNT exposure in humans. Research into the mechanisms by which CNTs induce pulmonary fibrosis is warranted in order to facilitate the understanding, monitoring, and treatment of CNT-induced lung lesions that might occur in exposed populations. The current study focuses on investigating the role of osteopontin (OPN) in the development of lung fibrosis upon exposure to multi-walled carbon nanotubes (MWCNTs). Methods C57BL/6J (WT) and Opn knockout (KO) mice were exposed to MWCNTs by pharyngeal aspiration to examine the acute and chronic effects of MWCNT exposure. The role of OPN and its mode of action in lung fibrosis development were analyzed at the cellular and molecular levels in vivo and in vitro. Results OPN was highly and persistently induced in both the acute and chronic phases of the response to MWCNT exposure in mouse lungs. Comparison between WT and Opn KO mice revealed that OPN critically regulated MWCNT-induced lung fibrosis as indicated by reduced fibrotic focus formation and myofibroblast accumulation in Opn KO lungs. At the molecular level, OPN promotes the expression and activation of TGF-β1, stimulates the differentiation of myofibroblasts from fibroblasts, and increases the production of fibrous matrix proteins in lungs and cultured lung cells exposed to MWCNTs. Conclusion OPN is highly induced in CNT-exposed lungs and plays critical roles in TGF-β1 signaling activation and myofibroblast differentiation to promote fibrosis development from MWCNT exposure. This study reveals an OPN-dependent mechanism to promote MWCNT-induced lung fibrosis. The findings raise the possibility of using OPN as a biomarker to monitor CNT exposure and as a drug target to halt fibrosis development.